PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBASIS GEOGLE SITE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IVSD NEGERI 16 PASARAN 1 NAINGGOLAN - Ferry Hendiko Sinaga; Patri Janson Silaban; Antonius Remigius Abi; Rumiris Lumban Gaol; Bogor Lumban Raja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the Google Site-based jigsaw type cooperative learning model on the mathematics learning outcomes of fourth grade elementary school students Negeri 16 markets 1 nainggolan 2023/2024 academic year. The research method used is an experimental method with a quantitative research type. To obtain the data required a test instrument of 30 questions. The total research sample was 26 students based on Random Sampling techniques. To determine students' initial abilities, the research conducted a Pre Test with an average score of 57.76 which was included in the poor category. The results of the Posttest have improved from the Pretest results given previously with the students' average score reaching 86.26 in the good category and the average score from the questionnaire being 83.42. It can be said that students' speaking skills have improved as evidenced by the results of the correlation coefficient test calculation, which obtained r_count ≥r_tabel with results of 0.722 ≥ 0.388. Next, hypothesis testing compares the t_count ≥t_table value. Obtained t_count value ≥t_table (5.115 ≥ 2.048) then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the Role Playing method (X) on students' speaking skills (Y).